The Internet Name Game Has Become Complicated. - MARGETTA, ROB (CQ Weekly, 2015)
This article discusses a provision in the omnibus appropriations bill the U.S. Congress passed in December 2014 which prohibits the government from giving up its international authority over domain names and numbers on the Internet. Topics discussed include the members of Congress who commented on the provision, including House of Representatives Judiciary Committee Chairman Robert W. Goodlatte, Republican-Virginia, and Committee member John Conyers Jr., Democrat-Michigan.